2014
DOI: 10.1177/0040517514549987
|View full text |Cite
|
Sign up to set email alerts
|

Study on negative Poisson’s ratio of auxetic yarn under tension: Part 2 – Experimental verification

Abstract: Auxetic yarn was successfully produced by a wrap filament and a core filament based on a ring-spinning system, which showed an auxetic effect when stretched, that is, expanding transversely under tension. Yarns were spun by different structural parameters of the core filament and the wrap filament, including diameter ratio, helical angle and tensile modulus of the wrap filament. Corresponding tensile tests were utilized to analyze the effects of structural parameters and performance on outer contour deformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
63
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(70 citation statements)
references
References 16 publications
(15 reference statements)
7
63
0
Order By: Relevance
“…It can be seen that DHY, 4‐ply, and 6‐ply auxetic yarns have a significant variation in auxetic behavior under stretching. DHY A‐1‐D has the same kind of Poisson's ratio‐strain curve and similar auxetic characteristics consistent with the references, that is, the Poisson's ratio is positive and increases with increasing tensile strain at the beginning of stretch, then decrease till its maximum negative value and finally increases toward zero until the yarn is broken. It is interesting to note that due to the core‐wrap structure of the DHY, the initial elongation is inevitably accompanied with a positive Poisson's ratio.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…It can be seen that DHY, 4‐ply, and 6‐ply auxetic yarns have a significant variation in auxetic behavior under stretching. DHY A‐1‐D has the same kind of Poisson's ratio‐strain curve and similar auxetic characteristics consistent with the references, that is, the Poisson's ratio is positive and increases with increasing tensile strain at the beginning of stretch, then decrease till its maximum negative value and finally increases toward zero until the yarn is broken. It is interesting to note that due to the core‐wrap structure of the DHY, the initial elongation is inevitably accompanied with a positive Poisson's ratio.…”
Section: Resultssupporting
confidence: 82%
“…Wright, Sloan and Evans carried out a finite element analysis and an experimental study to investigate the influence of structural and material parameters on the auxetic performance of the DHY . Du et al conducted a theoretical analysis to predict the auxetic performance of the DHY for any given tensile strain and an experimental study afterward to verify the accuracy of the model . Sibal and Rawal also proposed a DHY system to predict the auxetic behavior of the DHY through energy minimization approach .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that a lower initial wrap angle can lead to a larger maximum NPR. [20,21,[24][25][26] In contrast, there may also exist an critical angle for obtaining the largest NPR, below or above which the maximum NPR of HAY will be impeded. [22] With respect to the Poisson's ratio of core and stiff yarns, it is found that the auxetic effect of HAY is increased with the decrease in their Poisson's ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Bhattacharya et al 20 found that the core indentation effect (the wrap fiber embeds into the core fiber) would reduce the auxetic performance of the HAY; therefore, this phenomenon should be eliminated during the manufacturing process. Du et al 21,22 carried out theoretical and experimental studies to investigate the effect of different design parameters on the auxetic performance of HAY. Zhang et al 23 fabricated a novel three-component auxetic structure based on a HAY and they indicated that the coating thickness was identified as a new design parameter for tailoring the auxetic effect.…”
mentioning
confidence: 99%